Development of hi-rail vehicle driven on metre-gauge railway/road in Thailand - Viroch Sukontanakarn; Paanthong Sroymuk; Boonlit Pongsatitpat (Institute of Advanced Engineering and Science, 2022)
This research aims to develop a pickup truck to become a hi-rail vehicle that runs on meter gauge railways in Thailand. It is intended to be used for rails maintenance or response times during train derailments and for accessing inaccessible areas via rails in emergency situations. A hi-rail vehicle can travel both on rails and roads. The guide train steel wheels set is designed to have steel wheels running on rails with the vehicle being raised above the rails using a programmable logic controller for hydraulic cylinders. The results of the road test can run at a normal speed of not more than 90 kilometers per hour. The results of the test run on the rails can run at speed of not more than 30 kilometers per hour. There is a vibration of the hi-rail vehicle due to the designed guide train steel wheels set mechanism that can be accepted.